Developing Learning Materials of Islamic Education Integrated with Mathematics and Sains for Junior High School - Maria Ulpah; Sumiarti; Wan Alawee Samaeng (State Islamic Institute of Madura, 2023)
The design of learning materials and the learning process for Islamic Education subjects is ideally not only normative, but must also be combined with a scientific approach. An understanding of the concept of religion as a whole and integrated will cause students to have a complete world view of religion and science. Therefore, the purpose of this study is to develop learning materials of Islamic Education integrated with mathematics and science for junior high school. This study is research and development which consists of four stages, namely define, design, develop, and dissaminate. The data collecting techniques used are questionnaires to find out experts’ assessment and students’ respons. The results showed that the learning materials has fulfilled the requirements to be considered feasible to be used in the learning process.